A proportional power sharing method through a local control for a low-voltage islanded microgrid. (December 2022) - Azim, M. Imran; Ali, Liaqat; Peters, Jan; Shawon, Mohammad H.; Tatari, Fatemah R.; Muyeen, S.M.; Ghosh, Arindam
Abstract: In this paper, the proportional power sharing is focused through proposing a modified reverse droop control (RDC) scheme in a low-voltage (LV) islanded microgrid. The power is shared proportionally among parallel inverter-interfaced distributed energy resources (DERs) in an LV microgrid to distribute the change in the load based on their power capacity. The proposed control method shares real power inversely proportional in accordance with the real droop gain when the DERs have the same initial voltage values, while reactive power is also shared proportionally depending on reactive droop gains when different DERs' rate-of-change of voltage angles (i.e. system frequency) are equal. The stability margins of the droop gains are analysed by dint of extended dynamic phasor model (DPM). An LV microgrid with inverter-interfaced DERs is demonstrated to run simulations during load impedance changing scenario. The simulation results demonstrate that the proposed controller provides better response with lesser oscillations than the conventional reverse droop controller. Also, the performance of sharing power in an LV islanded microgrid is validated.